THE ROLE OF SPEECH THERAPY IN MODERN SPEECH THERAPY - Xonbabayeva Madinabonu Asqarjon qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article covers the role of speech therapy in modern Speech Therapy, information on the work carried out in this regard, especially the motivation of future speech therapists to acquire the skills of being able to apply their theoretical knowledge in practice in future activities.